The Age of Reason - Manuel, Frank E. (The Development of Western Civilization, 2019)
The period between the Peace of Utrecht and the French Revolution is brought into focus in this essay. Professor Manuel deals with the age of the philosophes and the enlightened despots, when belief in man's ability to achieve a good society through reason was in its first hopeful flower. The powerful pressures of that time are evaluated - the rapidly increasing population, the phenomenal growth of cities and industries, the greater facility of travel and transportation, The modern nation-state, as exemplified in France, England, the Hapsburg Empire, Prussia, and Russia, was growing strong and centralized. The relations of these states to one another are discussed.